Precautionary Demand for Money and Economic Uncertainty: Evidence from Toda-Yamamoto Long-Run Causality Method - Wu, Zhizi; Gan, Pei-Tha; Abd Hadi, Fatimah Salwa; Lim, Ee-Vern (International Journal of Economics and Financial Issues, 2025)
A notable feature of empirical studies on government unknown or uncertain policies influencing the economy that lead to the precautionary demand for money among economic agents is that very few studies put emphasis on causality inference, cross-country comparisons, and the integration of behavioral factors. To prevail over this shortcoming, this study examines the long-run causal relationship between the precautionary demand for money and economic uncertainty and the fear factor, without neglecting the roles of income and the interest rate in the money demand function in 28 economies. The empirical results from Toda-Yamamoto long-run causality method indicate that economic uncertainty and the fear factor demonstrate significant explanatory power for the precautionary demand for money, which policy maker could utilize in fine-tuning the liquidity provision for improved macroeconomic stability.